Ligands for Abasic Site-containing DNA and their Use as Fluorescent Probes - Schlosser, Julika; Ihmels, Heiko (Current Organic Synthesis, 2023)
Apurinic and apyrimidinic sites, also referred to as abasic or AP sites, are residues of duplex DNA in which one DNA base is removed from a Watson-Crick base pair. They are formed during the enzymatic repair of DNA and offer binding sites for a variety of guest molecules. Specifically, the AP site may bind an appropriate ligand as a substitute for the missing nucleic base, thus stabilizing the abasic site-containing DNA (AP-DNA). Notably, ligands that bind selectively to abasic sites may be employed for analytical and therapeutical purposes. As a result, there is a search for structural features that establish a strong and selective association of a given ligand with the abasic position in DNA. Against this background, this review provides an overview of the different classes of ligands for abasic site-containing DNA (AP-DNA). This review covers covalently binding substrates, namely amine and oxyamine derivatives, as well as ligands that bind to AP-DNA by noncovalent association, as represented by small heterocyclic aromatic compounds, metal-organic complexes, macrocyclic cyclophanes, and intercalator-nucleobase conjugates. As the systematic development of fluorescent probes for AP-DNA has been somewhat neglected so far, this review article contains a survey of the available reports on the fluorimetric response of the ligand upon binding to the AP-DNA. Based on these data, this compilation shall present a perspective for future developments of fluorescent probes for AP-DNA.
Keywords: cancer